Preparation of a new two-dimensional nanomaterial MXene and its application progress in energy storage - DANG A-lei; FANG Cheng-lin; ZHAO Zhao; ZHAO Ting-kai; LI Tie-hu; LI Hao (Cailiao gongcheng, 2020)
As a new type of two-dimensional nanomaterials, MXene has been widely investigated since its discovery at 2011 due to its excellent physical and chemical properties, such as high conductivity, good lubricity, electromagnetism and other special properties. Hence, in addition to the performance of the traditional two-dimensional materials, MXene has been extensively used in the fields of energy storage, catalysis, lubrication, electromagnetic shielding, sensor, water purification and so on,and certain results and progress were achieved. The latest researches of MXene at structure, property and preparation methods, as well as the related achievements in lithium ion battery, supercapacitor and others at our country and overseas in recent years were reviewed in this paper. Moreover, the shortcomings of current research were summarized, and the future research direction were prospected as well.